Editorial. - Borja Herrera, Amarilis (My University, 2015)
For the American composer Tom Waits “while there is research, there is hope”. This statement is, without a doubt, a great truth. Research is not only hope, but a reason to continue believing that there is something more to which we must aspire, not settle for what we have achieved, get out of our comfort zone and seek excellence from academic causes. For this reason, this noble alma mater called the Technical University of Machala, on its forty-sixth anniversary of creation, is more committed than ever to high-level research of each and every one of the actors, protagonists and social agents, producers of meaning and knowledge. , who make up the university community. Together we have embarked on a path that has no turning back and that demands and demands from us a greater critical, reflective, analytical and purposeful capacity to rethink the world and human experiences with an autonomous voice and a rigorous scientific approach. As we walk we make a path, a path that speaks of work, vocation and service.
Para el compositor estadounidense Tom Waits “mientras hay investigación, hay esperanza”. Esta afirmación es, sin lugar a dudas, una gran verdad. La investigación no sólo es esperanza, sino una razón para seguir creyendo que hay algo más a lo cual debemos aspirar, no conformarnos con lo alcanzado, salir de nuestra zona de confort y busca la excelencia de las causas académicas. Por ello, esta noble alma máter llamada Universidad Técnica de Machala, en su cuadragésimo sexto aniversario de creación está más comprometida que nunca con la investigación a alto nivel de todos y cada uno de los actores, protagonistas y agentes sociales, productores de sentido y conocimiento, quienes conforman la comunidad universitaria. Juntos hemos emprendido un camino que no tiene vuelta atrás y que nos exige y demanda mayor capacidad crítica, reflexiva, analítica y propositiva para repensar el mundo y las experiencias humanas con voz autónoma y una rigurosa cientificidad. Al andar hacemos camino, un camino que habla de trabajo, vocación y servicio.
Keywords: EDITORIAL; INVESTIGACIÓN